High-Quality Collaboration Benefits Teachers and Students. Lessons from Research - Killion, Joellen (Journal of Staff Development, 2015)
In this article, Joellen Killion highlights the methodology, analysis, findings, and limitations of Ronfeldt, M., Farmer, S., McQueen, K., & Grissom, J. (2015), "Teacher collaboration in instructional teams and student achievement," "American Educational Research Journal," 52(3), 475-514. Using sophisticated statistical analyses, researchers examined individual teacher-level and school-level collaboration to understand the nature and effects of teacher-to-teacher collaboration in instructional teams. When teachers engage in high-quality collaboration that they perceive as extensive and helpful, there is both an individual and collective benefit. High-quality collaboration in general and about assessment in particular among teachers is associated with increases in their students' achievement, their performance, and their peers' students' achievement.
Keywords: Academic Achievement; Educational Quality; Institutional Characteristics; Instructional Effectiveness; School Statistics; Statistical Analysis; Teacher Attitudes; Teacher Collaboration; Teacher Improvement; Teacher Surveys; Teamwork